Evaluating the Impact of Strategic Management Practices and Performance in Public Health Sector - Pradhan, Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
The recent restructuring in public administration because of new public management (NPM) has taken strategic management (SM) to the forefront of several public organizations. However, few studies examine how public organizations practice and which tools are used. Consequently, calls for such studies were made. In 2000s, the market transformation and pioneers in evolving tactics became the principal prerequisites for competitive dominance. Until recently, the traditional management and organizational strategies in place were inadequate to meet new rising demands. This study demonstrates the level of strategic management adopted by the management of health institutions. It is discussed in this study that if the management knows about strategic management tools that form the basis of strategic management applications, what strategic management tools they use, their satisfaction with them and what instruments they plan to use in the future. Additionally, changes in the field of strategic management, the priorities for choosing strategic management tools, the importance of strategic thinking and the impact on performance of strategic management understanding are discussed.